Falciparum malaria: differential effects of antimalarial drugs on ex vivo parasite viability during the critical early phase of therapy. - Watkins, WM; Woodrow, C; Marsh, K (1993)
A method of monitoring Plasmodium falciparum viability ex vivo was used to compare the ability of different antimalarial drugs to arrest the progression of young parasites to mature, potentially damaging stages. Neither pyrimethamine-sulfadoxine nor quinine, the treatment of choice for severe, life-threatening malaria, had a demonstrable effect on circulating parasites during the first 24 hr of therapy. In contrast, in vivo exposure to halofantrine for as little as six hours was sufficient to arrest parasite development. The method of assessing ex vivo parasite viability permits a comparison of antimalarial drug action at a time that may be critical for the therapy of life-threatening disease. If parenteral formulations of halofantrine prove to be safe and effective, they may have a role in the therapy of severe malaria.